Polymer matrix composites and technology - Wang, Rumin, 1962- (Woodhead Publishing in materials., 2011)
Given such properties as low density and high strength, polymer matrix composites have become a widely used material in the aerospace and other industries. Polymer matrix composites and technology provides a helpful overview of these materials, their processing and performance. After an introductory chapter, part one reviews the main reinforcement and matrix materials used as well as the nature of the interface between them. Part two discusses forming and molding technologies for polymer matrix composites. The final part of the book covers key aspects of performance, including tensile, compression, shear and bending properties as well as impact, fatigue and creep behaviour. Polymer matrix composites and technology provides both students and those in industry with a valuable introduction to and overview of this important class of materials. Provides a helpful overview of these materials, their processing and performance incorporating naming and classification of composite materialsReviews the main reinforcement and matrix materials used as well as the nature of the interface between them including damage mechanismsDiscusses forming and molding technologies for polymer matrix composites outlining various techniques and technologies.